NEUROPROTECTIVE ANTIOXIDANT EFFECT OF PORTULACA QUADRIFIDA LINN. LEAVES EXTRACT ON IMMOBILIZATION STRESS-INDUCED CHANGES IN RAT’S BRAIN - Shahwan, MOAYAD JAMAL; Gacem, Sabrina Ait (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The current study was established to illustrate the effect of this plant’s active constituents on stress-induced diseases that include oxidation damage to cellular components, especially the brain. Methods: Immobilization stress method is induced and initiated by putting separated animals in specially prepared mesh cages on a wooden plank. The animals were exposed to 6 h of stress. Wistar male rats were selected weighing (180â€“200 g). A total of 54 rats were selected and separated into nine groups and only six experimental rats were kept in each group. Results: The post-stress oral treatment of extract (100 mg/kg body weight) was more efficient in restricting stress-induced decline of superoxide dismutase (p<0.05), glutathione (GSH)-S-transferase (p<0.02), catalase (p<0.05), and GSH (p<0.05) and an enhanced level of thiobarbituric acid reactive substance (p<0.01) compared to stress alone or pre-stress extract treatments. Conclusion: The extract showed a significant resistance toward the oxidative metabolism triggered by restraint stress, though the post-extract treatment (curative) was observed to be more effective in restoring the altered oxidative metabolism compared with pre-extract treatment (prophylactic).